Building the Future : Mid- and Long-Term Vision for the Paraguay Health Sector Development, Final Report Executive Summary - World Bank (Washington, DC, 2014)
In 2009, the Paraguayan Government's Ministry of Health and the World Bank agreed to conduct technical cooperation work, which included two specific studies and an analysis of the public health sector, with a view to identifying medium- and long-term health sector policy formulation options. The specific studies were on: (i) the national pharmaceutical sector, and (ii) the social determinants of health. This study, facilitated technical exchanges and policy dialogue with the authorities throughout the process, which included the organization of workshops and the submission to the Ministry of Public Health and Social Welfare in December 2010 of two technical documents, one of which focused on the social determinants of health and the other, on drug policy, which are included in the annexes to this report; as well as to bring technical assessment to the Ministry of Public Health and Social Welfare about health services integrated networks. This report analyzes the available evidence on changes and trends in the state of health of the Paraguayan population through 2010 to 2011, taking into account the policy guidelines and institutional changes introduced during the final period of the government's term and the trends in a number of social determinants of health. This report will contribute to the development of a medium- and long-term strategy, with the ultimate aim of improving health outcomes, and will serve as a tool that provides information and recommendations that can also create new opportunities for collaboration in the area of sectoral dialogue in the country. This report discusses the following points: recent trends in the population health situation; policy guidelines since 2008; proposals: medium and long-term policy focal areas; health care system; and public health policies.